Immunohistochemical characterisation of cell-type specific expression of CK1delta in various tissues of young adult BALB/c mice. - Jürgen Löhler (Public Library of Science (PLoS), 2009)
Background Casein kinase 1 delta (CK1delta) phosphorylates many key proteins playing important roles in such biological processes as cell growth, differentiation, apoptosis, circadian rhythm and vesicle transport. Furthermore, deregulation of CK1delta has been linked to neurodegenerative diseases and cancer. In this study, the cell specific distribution of CK1delta in various tissues and organs of young adult BALB/c mice was analysed by immunohistochemistry. Methodology/principal findings Immunohistochemical staining of CK1delta was performed using three different antibodies against CK1delta. A high expression of CK1delta was found in a variety of tissues and organ systems and in several cell types of endodermal, mesodermal and ectodermal origin. Conclusions These results give an overview of the cell-type specific expression of CK1delta in different organs under normal conditions. Thus, they provide evidence for possible cell-type specific functions of CK1delta, where CK1delta can interact with and modulate the activity of key regulator proteins by site directed phosphorylation. Furthermore, they provide the basis for future analyses of CK1delta in these tissues.